Neurotrophic Effects of a Cyanine Dye via the PI3K-Akt Pathway: Attenuation of Motor Discoordination and Neurodegeneration in an Ataxic Animal Model - Ohta, Hitomi; Arai, Shigeyuki; Akita, Kenji; Ohta, Tsunetaka; Fukuda, Shigeharu (PLOS ONE, 2011)
Background Neurotrophic factors may be future therapeutic agents for neurodegenerative disease. In the screening of biologically active molecules for neurotrophic potency, we found that a photosensitizing cyanine dye, NK-4, had remarkable neurotrophic activities and was a potent radical scavenger. Methodology/Principal Findings In this study, we evaluated the effect of NK-4 on the protection of neurons against oxidative damage and investigated the associated intracellular signaling pathways. Subsequently, we evaluated the effect of NK-4 in an animal model of neurodegeneration. In vitro, NK-4 showed dose-dependent protection of PC12 cells from toxicity induced by oxidative stress caused by hydrogen peroxide (H2O2) or 6-hydroxydopamine (6-OHDA). Comparison of extracellular signal-regulated kinase signaling pathways between treatment with NK-4 and nerve growth factor (NGF) using K252a, an inhibitor of the NGF receptor TrkA, revealed that NK-4 activity occurs independently of NGF receptors. LY294002, a phosphatidylinositol 3-kinase (PI3K) inhibitor, blocked the protective effect of NK-4, and NK-4 caused activation of Akt/protein kinase B, a downstream effector of PI3K. These results suggest that the neuroprotective effects of NK-4 are mediated by the PI3K-Akt signaling pathway. NK-4 treatment also attenuated stress-induced activation of SAPK/JNK, which suggests that NK-4 activates a survival signaling pathway and inhibits stress-activated apoptotic pathways independently of the TrkA receptor in neuronal cells. In vivo, administration of NK-4 improved motor coordination in genetic ataxic hamsters, as assessed by rota-rod testing. Histological analysis showed that cerebellar atrophy was significantly attenuated by NK-4 treatment. Notably, the Purkinje cell count in the treated group was threefold higher than that in the vehicle group. Conclusions/Significance These results suggest that NK-4 is a potential agent for therapy for neurodegenerative disorders based on the activation of survival signaling pathways.